Hubungan Upaya Pemberantasan Sarang Nyamuk dengan Kejadian Demam Berdarah Dengue di Indonesia Tahun 2023 - Nofita Sari; Aulia Risqi Fatmariza (Ficco Public Health Journal, 2024)
Background: This study aims to identify the relationship between mosquito nest eradication efforts and the prevalence of dengue fever in Indonesia. Methods: The study used a quantitative method with a descriptive analytic design and a cross-sectional approach, where the independent variables (sowing larvicide powder, installing mosquito screens on vents, draining bathtubs, closing water reservoirs, and destroying used items) were analysed against the dependent variable, which was the prevalence of DHF based on the Indonesian Health Survey data in 2023. Data were analysed univariately and bivariately with Spearman correlation test to see the relationship between variables. Results: The results showed that installation of mosquito screens on house ventilation and destruction of used goods had a significant association with the prevalence of DHF (p=0.006 and p=0.042, respectively), while sowing larvicidal powder, draining bathtubs, and closing water reservoirs did not show a significant association. Conclusions: This study concludes that mosquito nest eradication efforts, particularly mosquito screen installation and disposal of used items, can be effective in reducing the prevalence of DHF in Indonesia.